Guidelines for development of marketing mix of natural attractions in Kanchanaburi Province - Ruamsup, Panwasa (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research aimed to: 1) compare the level of marketing mix of natural attractions in Kanchanaburi Province as classified by personal factors; 2) study the relationship between personal factors and natural tourism behavior in Kanchanaburi Province; and 3) study the guidelines for development of marketing mix of natural attractions in Kanchanaburi Province. The research sample was divided into 2 groups. The first group of questionnaire respondents consisted of 400 tourists who visited natural attractions in Kanchanaburi derived by quota sampling. The second group of interviewees consisted of 4 natural park officers at natural attractions in Kanchanaburi Province derived by purposive sampling. The research instruments were a questionnaire and an interview form constructed by the researcher, with the content validity between 0.66 and 1.00 and the reliability of 0.78 - 0.90. Data were analyzed with percentage, mean, standard deviation, t-test, one-way ANOVA, chi-square and content analysis. The research results revealed as follows: 1. The tourists with differences in gender, age and status had a different opinion on the marketing mix of natural attractions in Kanchanaburi Province with significant difference at .05 level. 2. The tourists’ personal factor in aspects of educational level, occupation, monthly income, status, and domicile had relationship with tourism behavior in aspects of travel purpose, travel method, number of companions, number of travels, travel period, relationship between companions, and travel expense with significant difference at .05 level. Additionally, the tourists’ gender showed relationship with tourism behavior in aspects of number of companions, number of travels, travel period, and travel expense with significant difference at .05 level. However, it showed no relationship with travel purpose, travel method, and relationship between companions. 3. The guidelines for development of marketing mix strategies of natural attractions in Kanchanaburi Province on the service providers’ views were: servicing by focusing on tourists’ satisfaction; setting fair price in accordance with experience value; increasing a variety of distribution channels; advertising tourist attractions through online media to ensure information accessibility; training tourism personnel about knowledge and understanding of natural attractions; and instilling awareness in service mindedness. Article history : Received 11 December 2018 Revised 14 April 2019 Accepted 17 April 2019 SIMILARITY INDEX = 3.13